2012
DOI: 10.12693/aphyspola.122.524
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Fe-Ni-Al-Si Alloys Produced by Powder Metallurgy

Abstract: Reactive sintering powder metallurgy is a simple alternative to conventional melting and powder metallurgy processes. During this process, pressed powder mixture of pure metals or other precursors is transformed into bulk intermediary phases by thermally activated in situ reaction. This process was previously tested on FeAl and FeAlSi alloys. Positive eect of silicon on the reactive sintering behaviour was determined, leading to the development of novel carbon-free high-silicon FeAl20Si20 alloy (given in wt%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Ni enables solid solution strengthening of the ferrite as a matrix without significantly reducing the elongation and toughness of the ferrite. Mo easily reacts with C to form carbides that act to refine the pearlite structure and increase the pearlite content [26][27][28][29]. In addition, trace elements such as P, Mn and Si also contribute to the optimisation of iron- based powder metallurgy materials [30,31].…”
Section: Raw Materials Distribution Ratiomentioning
confidence: 99%
“…Ni enables solid solution strengthening of the ferrite as a matrix without significantly reducing the elongation and toughness of the ferrite. Mo easily reacts with C to form carbides that act to refine the pearlite structure and increase the pearlite content [26][27][28][29]. In addition, trace elements such as P, Mn and Si also contribute to the optimisation of iron- based powder metallurgy materials [30,31].…”
Section: Raw Materials Distribution Ratiomentioning
confidence: 99%
“…Up to now, almost no reports have mentioned the influence of these elements on the microstructure and properties of quaternary and foremostly quinary alloys. Novák et al [24] reported that the addition of Ni in the FeAl20Si20 (wt %) alloy prepared by reactive synthesis resulted in a decrease of porosity while increasing the hardness and wear resistance as well as thermal stability and oxidation resistance at 800 • C. The same alloy, although prepared by mechanical alloying (MA) and compacted via spark plasma sintering (SPS), showed quite similar results, increasing the hardness and compressive strength from 1049 HV 1 up to 1376 HV 1 and from 1085 MPa up to over 1800 MPa [25].…”
Section: Introductionmentioning
confidence: 99%